In vitro Biological Activities and Phytochemical Contents of Portulaca oleracea L. (Purslane) - Keser, Fatma; Karatepe, Mustafa; Keser, Serhat; Tekin, Suat; Türkoğlu, İsmail; Kaygili, Omer; Kırbag, Sevda (Niyazi BULUT, 2021)
P. oleracea is an annual herbaceous plant, belonging to the Portulaceae family. This plant is consumed as a vegetable in Turkey, and is grows spontaneously in wetlands, along streams and meadows. In this study, the antiradical, antimicrobial, anticancer activities and phytochemical contents of aerial parts extracts of P. oleracea were investigated. According to study results, P. oleracea aerial part extracts show very high anticancer activity against MCF-7, HCT-116, A2780 and PC-3 cancer cell lines, high antiradical activity against OH radicals, and effective antimicrobial activity against some microorganisms. Also, it was determined that P. oleracea aerial parts contain highly phytochemical compounds. In conclusion, it can be said that the P. oleracea aerial parts can be used for antiradical, antimicrobial, anticancer purposes.
Keywords: Chemical Engineering; Kimya Mühendisliği